The Effect of Individual and Group Jump Rope Games on Physical Fittnes and Motivation - Abdul Rachman Syam T; Amrozi Khamidi; Moh. Yusroni (BIRCU, 2019)
This study aims to examine the effect of indifdual jump rope games and grouop jump rope on physical fitness and student motivation on futsal extracurricular students in MTs NU Berbek Waru Sidoarjo . This Study uses a quantitative approach to quasy expereriment research and the design ued is matching only design. The subjects of this study were 33 students who will be pretested to determine the division of groups. 11 students as the experimental group I were given the treatment of jump rope games individually and thefollowing 11 students as the experimental group II were reated as a group of jump rope games and the remeaning 11 studentswere made as a control group. Data collection methods in this study used two research instruments, namely the TKJI test to measure physical fitness scores and the motivation levels. Data werw analyzed with descriptive statistics using the SPSS 22.0 program. Based on the data obtained it can be concluded that there was a more significant increase in the two experimental groups compared to the control group. Physical fitness in all three groups experienced an increase, nmely by 6 % in group I, 9% in gropu II and 2 % in group III. Student motivation has increased by 3% while in group III student motivation has descread by 1%. The result of the study have proven that individual jump rope games and jump rope games in groups can improve the level of physicl fitness and motivation of students in following futsal extracurricular